GAMBARAN PENERAPAN HIGIENE SANITASI DAN DAMPAK KEBISINGAN PADA PEKERJA PENGGILINGAN BAKSO DAGING SAPI DI PASAR CIKURUBUK KOTA TASIKMALAYA TAHUN 2026 - Adzkia Nailatul Kamil; Salsabila Ayuningtyas; Azka Zikra Andini Wulandati; Puji Delya Lestari; Rismawati Rismawati; Siti Novianti (JURNAL ILMIAH NUSANTARA, 2026)
. Small-scale food processing industries, such as meatball grinding businesses, are vulnerable to sanitation hygiene problems and noise hazards. This study aimed to describe the implementation of sanitation hygiene practices and the impact of noise exposure on workers at Penggilingan Bakso Daging Sapi Kita in Tasikmalaya. The study employed a descriptive quantitative method with a cross-sectional design. A total of 36 respondents were selected using a total sampling technique. Data were collected through questionnaires and analyzed using univariate analysis. The results showed that the majority of respondents had a senior high school education background (77.8%) and were in the non-risk age category (58.3%). The implementation of workers’ sanitation hygiene practices was predominantly categorized as poor (61.1%), mainly due to the low use of Personal Protective Equipment (PPE). All respondents (100%) experienced the effects of noise exposure, with most categorized as experiencing moderate noise impact (55.6%). Based on research, it is recommended that business owners install sound dampers (mufflers) and require workers to use earplugs and complete PPE.